1. The problem statement, all variables and given/known data if light incident on a grating makes an angle phi with the normal of the grating, show that the equation m(lambda)=d(sin(theta)) becomes m(lambda)=d[sin(theta-phi)+sin(phi)] 2. Relevant equations m(lambda)=d(sin(theta)) d=spacing of slits, theta=angle displaced from normal of the grating m(lambda)=d[sin(theta-phi)+sin(phi)] 3. The attempt at a solution I've been working on trying to get a solution to this equation for quite some time now, and the only thing that makes sense is the equation m(lambda)=d*sin(theta-phi). don't know where +sin(phi) comes from.